Sodium bicarbonate and high-intensity-cycling capacity: variability in responses - Saunders, B.; Sale, C.; Harris, R. C.; Sunderland, C. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To determine whether gastrointestinal (GI) distress affects the ergogenicity of sodium bicarbonate and whether the degree of alkalemia or other metabolic responses is different between individuals who improve exercise capacity and those who do not. Methods: Twenty-one men completed 2 cycling-capacity tests at 110% of maximum power output. Participants were supplemented with 0.3 g/kg body mass of either placebo (maltodextrin) or sodium bicarbonate (SB). Blood pH, bicarbonate, base excess, and lactate were determined at baseline, preexercise, immediately postexercise, and 5 min postexercise. Results: SB supplementation did not significantly increase total work done (TWD; P = .16, 46.8 ± 9.1 vs 45.6 ± 8.4 kJ, d = 0.14), although magnitude-based inferences suggested a 63% likelihood of a positive effect. When data were analyzed without 4 participants who experienced GI discomfort, TWD (P = .01) was significantly improved with SB. Immediately postexercise blood lactate was higher in SB for the individuals who improved but not for those who did not. There were also differences in the preexercise-to-postexercise change in blood pH, bicarbonate, and base excess between individuals who improved and those who did not. Conclusions: SB improved high-intensity-cycling capacity but only with the exclusion of participants experiencing GI discomfort. Differences in blood responses suggest that SB may not be beneficial to all individuals. Magnitude-based inferences suggested that the exercise effects are unlikely to be negative; therefore, individuals should determine whether they respond well to SB supplementation before competition.